2018
DOI: 10.3390/children5100129
|View full text |Cite
|
Sign up to set email alerts
|

School Bag Weight as a Barrier to Active Transport to School among New Zealand Adolescents

Abstract: Background: Excessive school bag weight is a barrier to active transport to school (ATS). This study examined parents’ and adolescents’ perceptions of school bag weights and actual school bag weights for adolescents in New Zealand. Methods: Parents (n = 331; 76.7% women) completed a survey. Adolescents (n = 682; age 15.1 ± 1.4 years; 57.3% boys) completed a survey, underwent anthropometry, and had their school bags weighed. Results: Overall, 68.3% of parents perceived that adolescents’ school bags were too hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
1
20
0
4
Order By: Relevance
“…At the time of the survey, research assistants weighed adolescents’ school bags using a digital electronic scale (A&D scale UC321, A&D Medical, San Jose, CA, USA), as described previously [ 21 ]. School bag measurements included the weight of each adolescents’ school bags without an electronic device and, if applicable, a separate weight measurement of their electronic device and/or any additional bags, including sports gear and/or musical instruments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of the survey, research assistants weighed adolescents’ school bags using a digital electronic scale (A&D scale UC321, A&D Medical, San Jose, CA, USA), as described previously [ 21 ]. School bag measurements included the weight of each adolescents’ school bags without an electronic device and, if applicable, a separate weight measurement of their electronic device and/or any additional bags, including sports gear and/or musical instruments.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, actual and perceived school bag weight may influence adolescents’ and their parents’ decisions as to whether adolescents walk and/or cycle to school. A New Zealand study conducted in an urban setting found that approximately two-thirds of parents perceived that adolescents’ school bags were too heavy to carry to school, and nearly two-thirds of adolescents perceived their school bags as too heavy to carry for walking or cycling to school [ 21 ]. Compared to active transport users, a greater proportion of adolescents and parents who used motorised transport to school perceived adolescents’ school bag weights as a barrier for walking or cycling to school, whereas the measured school bag weight did not differ between adolescents using active, motorised, or mixed modes of transport to school [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Body mass index will be calculated and weight status category will be determined using international age and genderspecific cut-points. 57 Adolescents' school bags will be weighed, 45 including a separate weighing of laptop computers/tablets, for students who bring them to school.…”
Section: Anthropometry Measurementsmentioning
confidence: 99%
“…It represents a simple method of incorporating PA in the form of walking or cycling into everyday life. Despite its advantages, AC is still underused, which might be due to less supportive built environments [20], parents' preferred travel options [12,13], cultural differences [21], and/or other factors [22]. The proportion of Czech adolescents commuting to school actively has been decreasing.…”
Section: Introductionmentioning
confidence: 99%